Contrastive Analysis of Terminological Phrasemes With Colour Components in English, French, Italian and Slovak. Field of Economy and Finance - Dinžíková, Iveta
Kontrastívna frazeológia. Typológia rovnocennosti fráz. Symbolizácia farieb. Čierna ako symbol.